Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fenrg.2018.00053
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Rheological Method to Evaluate Feedstock Physical Properties Throughout Enzymatic Deconstruction

Abstract: Feedstock physical properties determine not only downstream flow behavior, but also downstream process yields. Enzymatic treatment of pretreated feedstocks is greatly dependent on upstream feedstock physical properties and choice of pre-processing Technologies. Currently available enzyme assays have been developed to study biomass slurries at low concentrations of ≤1% w/w. At commercially relevant biomass concentrations of ≥15% w/w, pretreated feedstocks have sludge-like properties, where low free water restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…When the phase angle is higher than 45°, materials present liquid-like behavior and vice versa. 132 Typically, a high solids loading (less use of water) reduces heating requirements and downstream product dilution and thereby reduces processing cost. 135−137 However, increasing solids concentration also leads to high yield stresses and viscosities, 138,139 which introduces challenges in catalyst mass transfer and biomass transfer from one treatment operation to another.…”
Section: ■ Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…When the phase angle is higher than 45°, materials present liquid-like behavior and vice versa. 132 Typically, a high solids loading (less use of water) reduces heating requirements and downstream product dilution and thereby reduces processing cost. 135−137 However, increasing solids concentration also leads to high yield stresses and viscosities, 138,139 which introduces challenges in catalyst mass transfer and biomass transfer from one treatment operation to another.…”
Section: ■ Mechanical Propertiesmentioning
confidence: 99%
“…The study of viscoelastic properties of biomass before and after pretreatment and enzymatic hydrolysis provides an indication of flow behaviors. Rotational rheometers, torque rheometry, and oscillatory rheometry are commonly used to explore the viscoelastic properties, yield stress, viscosity curves, and compliance of pretreated biomass. Capillary rheology is used to characterize important physical phenomena, such as liquid phase migration . Three interrelated parameterselastic modulus, viscous modulus, and phase angleare measured to study viscoelastic properties.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, no effect was observed in the enzymatic hydrolysis of microcrystalline cellulose at 2% upon the addition of 10-35 mg of corn stover purified lignin per gram of cellulose [68] or of AFEX pretreated corn stover at increasing amounts of solids of 13.8, 19.3, and 24.9% [91]. Moreover, results from the enzymatic hydrolysis of 1% sugarcane bagasse treated by ball milling, a physical pretreatment that da Silva et al Biotechnol Biofuels (2020) 13:58 decreases cellulose crystallinity while keeping the native biomass composition, showed hydrolysis yields as high as 91% following 24 h of hydrolysis [92]; other researchers have also reported high biomass conversion yields in the presence of lignin [77,93,94]. Huang et al [94] observed that the hydrolysis yield was improved by 8-12% or decreased by 6-16% depending on the biomass source and pretreatment conditions that produced lignins with different characteristics.…”
Section: Effect Of Lignin and Pseudo-lignin On Enzyme Efficiencymentioning
confidence: 99%
“…These authors characterized each biomass and suggested that the lignin inhibition or stimulation effect is controlled by lignin hydrophobicity and the negative zeta potential, respectively. Still, Coffman et al [93] reported that the enzymatic hydrolysis of Avicel was faster in the presence of lignin. It is important to emphasize that these reports used an enzyme preparation containing LPMOs, which could be responsible for the boosting effect, as suggested by Cannella et al [77].…”
Section: Effect Of Lignin and Pseudo-lignin On Enzyme Efficiencymentioning
confidence: 99%